School-Based Management as an Innovation in Improving the Quality of Education - Waode Zahra Februannisa; Nisa Juniar Anggraini (Journal of Quality Assurance in Islamic Education (JQAIE), 2022)
Educational innovation is a renewal in education and is different from the previous situation which was deliberately sought to solve educational problems in order to achieve educational goals optimally. Educational innovation boils down to the excellence or quality of education units in providing services to stakeholders. Quality improvement is an important program of education both on a national, regional, and international scale. The methods used in this research are critical analysis methods and literature methods. School-Based Management (SBM) is a management model that gives schools the right of autonomy to manage their schools independently and is also a form of changing education from poor conditions to better conditions by giving authority to schools to empower themselves. In order for the implementation of school-based management to run efficiently and effectively, cooperation between all components of education is needed and the availability of adequate advice and infrastructure.